FORMATION OF INFORMATION AND COMMUNICATION READINESS OF TEACHERS OF PRESCHOOL EDUCATION IN THE CONDITIONS OF CONTINUING PROFESSIONAL EDUCATION (Scientific journal of the Fergana State University, 2024)
The article is devoted to the formation of information and communication readiness of preschool teachers in the conditions of continuing professional education in Kyrgyzstan. The main problems and challenges faced by teachers in this field are highlighted, including insufficient training programs and materials, limited access to technical means and the Internet, as well as poor quality and availability of educational resources.The methods of teaching teachers the basics of ICT, specialized training on the use of ICT in the educational process, as well as the importance of teaching digital literacy and security are discussed.In conclusion, the need for further research and development of strategies and techniques to overcome the problems associated with the formation of information and communication readiness of preschool teachers in the conditions of continuing professional education in Kyrgyzstan is emphasized.